THE INFLUENCE OF GUIDANCE COUNSELING TEACHER ATTENDING SKILLS (BK) ON STUDENT OPENNESS IN INDIVIDUAL COUNSELING IN CLASS VIII-A UPTD SMP NEGERI 3 NORTH MANDREHE YEAR 2021/2022 - Mesrawati Lahagu (CV. Asy Persada Quality, 2024)
The purpose of writing this article is to find out whether there is an influence of guidance and counseling teachers' attending skills on students' openness in individual counseling in class VIII-A UPTD SMP Negeri 3 Mandrehe Utara. This research uses a quantitative research method with a correlational design type that describes the influence of guidance and counseling teachers' attending skills on students' openness in individual counseling in Class VIII-A UPTD of SMP Negeri 3 Mandrehe Utara. According to Sugiyono (2015) quantitative research methods can be interpreted as research methods that are based on the philosophy of positivism, used to research certain populations and samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical with The aim is to test the hypothesis that has been set. Based on data analysis, it is known that the results of research data analysis confirm that there is an influence of attending guidance counselors on students' openness and the contribution of variable the remaining 59% are items that influence openness that are not included in the research studied.